Effects of norepinephrine on plaque hypoxia in atherosclerotic rabbits - Wang, Jia-Yu; Liu, Kun; Wang, Yu-Bo; Deng, You-Bin; Sun, Jie (Frontiers in Cardiovascular Medicine, 2023)
Background: Hypoxia plays a vital role throughout the whole process of atherosclerotic vulnerable plaque formation, which may be induced by a reduced oxygen supply. The vasa vasorum can be affected by norepinephrine (NE) and cause a reduced oxygen supply, ultimately leading to plaque hypoxia. This study aimed to investigate the effects of norepinephrine, which can increase the tension of the vasa vasorum, on plaque hypoxia, evaluated by contrast-enhanced ultrasound imaging. Methods: Atherosclerosis (AS) was induced in New Zealand white rabbits by a combination of a cholesterol-rich diet and aortic balloon dilation. After the atherosclerotic model was well established, NE was intravenously administered three times per day for two weeks. Contrast-enhanced ultrasound (CEUS)and immunohistochemistry staining were performed to evaluate the expression of hypoxia-inducible factor alpha (HIF-α) and vascular endothelial growth factor (VEGF) in atherosclerotic plaques. Results: The plaque blood flow decreased after long-term norepinephrine administration. The expression of HIF-α and VEGF in atherosclerotic plaques concentrated in the outer medial layers increased, which indicated that NE might cause plaque hypoxia by contraction of the vasa vasorum. Conclusions: Apparent hypoxia of atherosclerotic plaques after long-term NE administration was mainly caused by decreased plaque blood flow due to the contraction of the vasa vasorum and high blood pressure.